Axial structure of DC glow discharge negative glow in nitrogen - Lisovskiy, V.A.; Derevyanko, V.A.; Kravchenko, E.A.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2012)
We registered axial profiles of electron temperature, plasma potential and concentration of the direct current glow discharge in nitrogen at different gas pressure and discharge current values. We observed that in a broad range of experimental conditions the plasma concentration experiences 15…16 times decrease along the negative glow length. Maximum values of plasma concentration and electron temperature are registered at the cathode end of the negative glow, and the electric field strength is small. On leaving the cathode the plasma concentration and electron temperature in the negative glow are decreasing, here a region with a negative field may also form. Осевые профили температуры электронов, потенциала и плотности плазмы тлеющего разряда постоянного тока в азоте измерены методом ленгмюровского зонда при различных значениях давления газа и разрядного тока. Показано, что в широком диапазоне экспериментальных условий на длине отрицательного свечения плотность плазмы уменьшается в 15-16 раз. Максимальные плотность плазмы и температура электронов наблюдаются на катодном конце отрицательного свечения, а напряженность электрического поля мала. При удалении от катода плотность плазмы и температура электронов в отрицательном свечении уменьшаются, здесь же может сформироваться область с отрицательным полем. Осьові профілі температури електронів, потенціалу і густини плазми тліючого розряду постійного струму в азоті виміряні методом ленгмюрівського зонда при різних значеннях тиску газу і розрядного струму. Показано, що в широкому діапазоні експериментальних умов на довжині негативного світіння густина плазми зменшується в 15-16 разів. Максимальні густина плазми і температура електронів спостерігаються на катодному кінці негативного світіння, а напруженість електричного поля мала. При віддаленні від катода густина плазми і температура електронів в негативному світінні зменшуються, тут же може сформуватися область із негативним полем.